ADDITION OF ALUMINUM OXIDE NANO PARTICLES TO THE ABSORBER PLATE COATING TO INCREASE THE PRODUCTIVITY OF SOLAR DISTILLATION - Caturwati, Ni Ketut; Sukamto, Dwinanto; Fauzi, Rizki (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Water is a natural resource that is very important for life in the world, especially for humans and other living things. There are few areas in Indonesia that have unsuitable water due to water pollution and limited fresh water source. Distillation is an effective way to produce clean water that is free from impurities in the form of small solids, germs and bacteria. One type of distillation systems is a solar distillation. However, the use of these still has low productivity. There are several ways to increase the productivity of solar distillation systems, one of them is by adding thermal energy storage material such as aluminum oxide (Al2O3) nanoparticles. This study based on experimental method by comparing a solar distillation systems with the addition of Al2O3 nanoparticles on the absorber plate coating to the coating without the addition of Al2O3. The test results showed that the addition of Al2O3 nanoparticles increased the productivity of solar distillation. The results show the addition of mass concentration of Al2O3 (nano particles): 10%; 15% and 20% , increased distillate production by: 44.73%; 88.98% and 134.85% compared without the addition of nanoparticles to the absorber plate coating.